Development of E-Comics Material on The Digestive System for Class XI High School - Vega, Nadya Maharani; Arsal, Andi Faridah; Syamsiah, Syamsiah (Biology Teaching and Learning, 2024)
Abstract. E-comic learning media is one of the educational innovations in an effort to increase students' interest in reading. The study aims to produce valid e-comic learning media on the digestive system material for class XI SMA. The type of research is research and development (Research and Development) using the ADDIE development model. The study was conducted in August 2023-June 2024 at SMAN 12 Maros. The subjects of the study were 2 biology teachers of class XI and 31 students of class XII MIPA 2 SMAN 12 Maros. The research instruments were interview sheets and questionnaire sheets. Data analysis techniques in the study, namely qualitative and quantitative analysis. The validity of the product is assessed by the validator. The assessment criteria used consist of five aspects, namely aspects of content/content feasibility, presentation, problem-solving skills, language, and accessibility of media use. The results of the study showed that the assessment of the two validators was 88.33% which was in the very valid category so that the e-comic learning media on the digestive system material for class XI SMA was suitable for use in learning. Keywords: Electronic Comics, Instructional Media, ADDIE Model, Digestive System